2022
DOI: 10.1155/2022/2848565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anterior Chamber Instability during Phacoemulsification Combined with Intraocular Lens Implantation

Abstract: Purpose. To determine the incidence of anterior chamber (AC) instability during phacoemulsification (phaco) combined with intraocular lens implantation and investigate its effect on intraocular tissues. Methods. Among the 248 enrolled eyes, 121 and 127 eyes were categorized into the irrigation and nonirrigation groups, respectively, depending on the use of a self-made anterior chamber maintainer (ACM) during phaco. AC stability was evaluated using operating microscopy and intraoperative optical coherence tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…However, most intraoperative leakage may not receive sufficient attention from surgeons probably because these subtle changes are difficult to observe under surgical microscope with coaxial illumination. By using the external slit illuminator on the surgical microscope, we found that anterior chamber collapse immediately after the withdrawal of the handpiece is more common than expected, in accordance with a previous study . This collapse might cause rapid forward movement of the iris lens diaphragm and contact between the corneal endothelium and IOL or posterior capsule immediately (Video).…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, most intraoperative leakage may not receive sufficient attention from surgeons probably because these subtle changes are difficult to observe under surgical microscope with coaxial illumination. By using the external slit illuminator on the surgical microscope, we found that anterior chamber collapse immediately after the withdrawal of the handpiece is more common than expected, in accordance with a previous study . This collapse might cause rapid forward movement of the iris lens diaphragm and contact between the corneal endothelium and IOL or posterior capsule immediately (Video).…”
Section: Introductionsupporting
confidence: 89%
“…Reformation of the anterior chamber had to be performed prior to stromal hydration. Indeed, there are several alternative methods to prevent anterior chamber collapse after the final removal of OVD, such as using an anterior chamber maintainer, performing stromal hydration beforehand, and removing OVD through paracenteses in bimanual fashion. Swab pressing still shows potential to be applied at each time when the handpiece is withdrawn to prevent intraoperative incision leakage responsible for transients collapse of anterior chamber.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 To achieve a safe cortex aspiration, a stable anterior chamber (AC) is mandatory. 2 One common reason for fluctuation of the depth of the AC and the fluttering of the posterior capsule is the outflow of fluid through the side port. This unavoidable leakage may occur even when the size of the side port is equal to that of the irrigation probe.…”
Section: Introductionmentioning
confidence: 99%